Glucagon-like Peptide-1 Receptor Agonists and Suicidal Ideation: Analysis of Real-Word Data Collected in the European Pharmacovigilance Database - Rosanna Ruggiero; Annamaria Mascolo; Angela Spezzaferri; Claudia Carpentieri; Daniele Torella; Liberata Sportiello; Francesco Rossi; Giuseppe Paolisso; Annalisa Capuano (MDPI AG, 2024)
Background: A potential risk of suicide associated with liraglutide or semaglutide treatments has recently emerged. Therefore, we decided to investigate the reporting probability of suicidal events among glucagon-like peptide-1 receptor agonists (GLP-1 RAs). Methods: A retrospective pharmacovigilance study of the European Pharmacovigilance database was conducted for the period from 1 January 2018 to 10 July 2023. Disproportionality analyses (reporting odds ratio, ROR) were performed to assess the reporting probability of suicidal events among GLP-1 RAs. Results: A total of 230 reports of suicidal events were identified. The most reported GLP-1 RA was liraglutide (38.3%), followed by semaglutide (36.5%) and dulaglutide (16.1%). The most reported events were suicidal ideation (65.3%) and suicide attempt (19.5%). Disproportionality analysis found a higher reporting probability of suicidal events for semaglutide than dulaglutide (ROR, 2.05; 95%CI, 1.40-3.01) and exenatide (ROR, 1.81; 95%CI, 1.08-3.05). In the same way, liraglutide was associated with a higher reporting probability of suicidal events than dulaglutide (ROR, 3.98; 95%CI, 2.73-5.82) and exenatide (ROR, 3.52; 95%CI, 2.10-5.92). On the contrary, a lower reporting probability was found for semaglutide than liraglutide (ROR, 0.51; 95%CI, 0.38-0.69). Conclusions: Suicidal events were mostly reported with semaglutide and liraglutide, which were also associated with significantly higher reporting probabilities compared to other GLP1 RAs. Although this study provides the reporting frequencies of suicide-related events with GLP-1 RAs, establishing causality requires further investigation, which will probably be addressed by the Pharmacovigilance Risk Assessment Committee of the European Medicine Agency in the future.